Contributions and Challenges in Health Psychology in the Treatment of Essential Arterial Hypertension - Molerio Pérez, Osana; García Romagosa, Georgina (Revista de Psicología, 2004)
Hypertensive disorders have a great relevance in our environment not only because of their high incidence, but also because of its role as a factor of risk of the brain and cardiovascular disorders. In this work we show the results of research in health psychology which caracterize the role of psychosocial factors in the genesis and evolution of arterial hypertension (HTA) which show the need for analysis by a multidisciplinary team, directed to hypertension patients. Finally the work suggests some questions related to health Psychology.